2013
DOI: 10.2147/opth.s51740
|View full text |Cite
|
Sign up to set email alerts
|

Case report of a neonate with ocular toxoplasmosis due to congenital infection: estimation of the percentage of ocular toxoplasmosis in Greece caused by congenital or acquired infection

Abstract: We report a case of a newborn male child with congenital toxoplasmosis. During pregnancy seroconversion occurred and positive titers of antitoxoplasmic antibodies (immunoglobulin M and G) were found in the mother, in the third trimester. She received treatment with spiramycin. After birth, the neonate presented with chorioretinitis and intracranial calcifications. The neonate received treatment with pyrimethamine, sulfadiazine, and leucovorin for 1 year. In addition to using a previously described method, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Important to note, the newborns with vertical T. gondii transmission usually have a normal appearance and thus congenital toxoplasmosis is not diagnosed and treated in the first years of life. They later, however, may develop chorioretinitis or neurologic and developmental deficits [ 9 ]. Furthermore, in patients with profound T-cell immunodeficiency toxoplasmosis may manifest as potentially fatal encephalitis, pneumonitis, myocarditis and eye diseases, mostly retinochoroiditis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Important to note, the newborns with vertical T. gondii transmission usually have a normal appearance and thus congenital toxoplasmosis is not diagnosed and treated in the first years of life. They later, however, may develop chorioretinitis or neurologic and developmental deficits [ 9 ]. Furthermore, in patients with profound T-cell immunodeficiency toxoplasmosis may manifest as potentially fatal encephalitis, pneumonitis, myocarditis and eye diseases, mostly retinochoroiditis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a better understanding of time-dependent factors is required. Particularly, the methods of studying the rates of recurrence are studied need to be very carefully assessed [ 144 ].…”
Section: Methodsmentioning
confidence: 99%
“…1,6,7 With regard to the efficacy of treatment on pathological sequelae, the European Multicentre Study of Congenital Toxoplasmosis (EMSCOT) found a reduction in neurological disease such as intracranial lesions, but no reduction in ocular disease risk if prenatal treatment is performed. 5 There were some ocular sequelae risk factors identified, particularly with regard to risk of developing RC. One study found that prematurity, non-ocular CT lesions present at baseline, and confirmed CT diagnosis in early maternal infection were all risk factors for the development of RC.…”
Section: Vertical Transmissionmentioning
confidence: 99%
“…1 Vertical transmission rates are estimated to be less than 10% in the first trimester with typically much more severe CT manifestations compared with a transmission rate of greater than 60% in the third trimester with typically less severe disease in child. 5 Other factors that seem to increase risk of mother-to-child transmission are acute maternal infection during pregnancy, maternal immunocompromise, increased strain virulence, increased parasitic load, and lack of antepartum treatment. 1 In Europe, where prenatal and neonatal screening is mandatory, several centers have studied the benefits of early diagnosis and treatment of toxoplasmosis infection for the health of the child.…”
Section: Vertical Transmissionmentioning
confidence: 99%
See 1 more Smart Citation